KHUMUS DALAM PERSPEKTIF MAZHAB JA’FARI - Dede Rodin (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2013)
In Islamic tradition, khums (literally one fifth of gain) refers to a religious obligation to contribute one-fifth of a certain type of income to charity. The obligatory giving of alms is observed throughout Islam and is one of the Five Pillars of the faith, but the nature of the tax varies considerably between various Islamic traditions. Khums is paid on all items regarded as ganima. There are differing legal traditions within Islam about what constitutes ganima, and thus how far-reaching khums should be. In certain Shia traditions (Ja’fari) ganima is defined as the year’s profit, including all net income and wealth left over at the end of a year. Within these traditions, Khums involves an annual taxation of one-fifth of all gain, and can be compared to a tithe, or an income tax. Khums includes the zakat, or alms required as one of the five pillaras of Islam.In Sunni tradition, ganima is defined as the spoils of war, and the tradition of paying khums has lapsed. However, Sunnis pay zakat, which involves a one-fortieth taxation of total wealth (and is more akin to a property tax). According to the hadiths of the Ahl al-Bayt Imams, the items that are eligible for khums are seven, and they are: (1) the profit or the surplus of income, (2) the legitimate wealth which is mixed with the illegitimate wealth, (3) mines and minerals, (4) the precious stones obtained from sea by diving, (5) treasures, (6) the land which a dhimmi kafir buys from a Muslim, and (7) the spoils of war.in the Ja’fari school, khums should go to six people: Allah, His Messenger, The near relative of the Messenger (Ahlul-Bayt), Orphan, needy, the person who has fallen away from his home-town (and has no money to comeback to his own place).